The Berliner-Studienberechtigten-Panel (Best Up): Methodological and data report - Martin Ehlert; Frauke Peter; Claudia Finger; Alessandra Rusconi; Heike Solga; Christa Katharina Spieß; Vaishali Zambre (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
[Introduction and research goals] Students whose parents do not have a college degree are still underrepresented at German universities, although many graduate from high school with a college entrance qualification. Why is this the case and what are possible policy measures that might increase their college enrollment? Why are students from so-called non-academic backgrounds more likely to pursue vocational education and training (VET)? These and other related questions are explored in a joint research project of the DIW Berlin and the WZB, which builds on a unique data set called “Berliner-Studienberechtigten-Panel (Best Up).” This research project was funded by the Einstein Foundation Berlin. The Principal investigators are Heike Solga (WZB and Freie Universität Berlin) and C. Katharina Spiess (DIW Berlin and Freie Universität Berlin); the project is coordinated by Frauke Peter at the DIW Berlin and Alessandra Rusconi at the WZB. [...]
Keywords: 330